Implementation of Government Regulation Number 20 Year 2021 Concerning Control of Study Abandoned Area and Land on HGB Land Indicted as Abandoned Land in Madiun City - Brilliant Setyo Pambudi; Suhariningsih Suhariningsih; Fathul Laila (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This abstract is entitled "Implementation of Government Regulation Number 20 of 2021 concerning Control of Study Abandoned Areas and Lands on HGB Land Indicated as Abandoned as Land in Madiun City". This research is a type of legal research with empirical research methods. Besides, this research uses a juridical-sociological research approach. The results of this abstract study Abandoned Land is land that is not used, not cultivated, not used according to its designation. In fact, land in Indonesia must function socially and benefit many people around it. The implementation of the control of Abandoned Land in Madiun City has been carried out with reference to Government Regulation Number 20 of 2021, namely concerning Control of Abandoned Areas and Lands. There are 108 lands indicated to be abandoned and 4 of them are certified with Hak Guna Bangunan. In the implementation it has been carried out properly and maximally, namely by socializing in advance regarding Government Regulation Number 20 of 2021, namely concerning Control of Abandoned Areas and Lands and continuing to be investigated regarding abandoned land, only in this implementation there is still an update of new regulations related to object exceptions. abandoned land, namely the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 20 of 2021 concerning.